The Correlation between Students’ Mastery in Simple Past Tense with the Ability of Writing Recount Text (The Correlational Study of the Tenth Year Students of SMA Pembangunan Lab UNP) - Oktavia Murdani; Mukhaiyar Mukhaiyar (Journal of English Language Teaching, 2020)
Simple past tense is usually used to express an action or condition that occurred in or during the past time. Simple past tense refers to complete action that occured in the past. Since the purpose of recount text is to retell our experiences or event that happened in the past, past tense should be utilized in the text. Students can use severel tenses to write about the past condition, but the simple past tense is often used dominantly. Based on the research question mentioned previously, the purpose of this research as follow is to find out whether there is a correlation between simple past tense mastery and writing recount text ability of tenth graders students in SMA Pembangunan Lab UNP. The researcher will use quantitative method since the data concerned appears numbering. The researcher chose one class from seven classes of tenth grade students of SMA Pembangunan Lab UNP in the academic year of 2019/2020. The class that the writer chose was class which learned English Peminatan Program. The writer wants to observe namely students’ mastery in past tense and their ability in writing recount, two instruments are utilized. Both are in the form of test. And in this study the writer used two types of tests; objective test in the form of completion test and cloze test to test students’ past tense mastery and essay type test for testing students writing ability. To find out whether or not there is a relationship between students’ mastery of past tense and their ability in writing recount, the correlation coefficient showing the degree as well as the direction of the relationship between the two variables being investigated will be computed. Because there was always a possibility that the result of the study will show no relationship between the variables, the following Pearson Product Moment Correlation was used.